1999
DOI: 10.1046/j.1365-2923.1999.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical faculty physicians about taking occupational history

Abstract: We found that physicians were not in the habit of taking occupational histories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…If one or more of these questions reveal any relation, then detailed occupational history must be taken for definitive diagnosis [4]. It has been shown in a variety of studies that taking occupational history and asking about occupation and exposure is very low during daily practice in patient examinations [5,6,7]. One of the most important reason is the lack of knowledge of physicians in establishing relationship between diseases and occupation and taking occupational history.…”
Section: Discussionmentioning
confidence: 99%
“…If one or more of these questions reveal any relation, then detailed occupational history must be taken for definitive diagnosis [4]. It has been shown in a variety of studies that taking occupational history and asking about occupation and exposure is very low during daily practice in patient examinations [5,6,7]. One of the most important reason is the lack of knowledge of physicians in establishing relationship between diseases and occupation and taking occupational history.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Most often, work-related diseases are underdiagnosed due to deficient occupational histories, with many illnesses of known occupational causes being ascribed to other causes or conditions. [13] Furthermore, severe sentinel health events and those involving a large number of exposed individuals may be reported to the concerned health departments or regulatory agencies as a useful control measure. [14]…”
mentioning
confidence: 99%
“…[17] It is, therefore, alarming that even with such a concerted pitch for routine occupational and environmental history taking; it still has not found a way into the mainstream. In a study conducted among physicians in a medical facility in Turkey by Cimrin et al .,[13] it was reported that 43.9% (29/69) physicians did not take an occupational history at all, with only 22.7% (15/69) taking a detailed occupational history from all patients. Routine taking of occupational history is believed to enhance the physician's knowledge of occupational medicine and the ability to practice preventive medicine and intervene in the interest of the health of the patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When an occupational history is taken, it tends to be insufficient in terms of the information gathered. The lack of occupational histories therefore contributes to the underreporting and under-recognition of occupational diseases (Cimrin et al, 1999;Lax et al, 1998;Taiwo et al, 2010).…”
Section: Absences In Medical Knowledge and Practice: Occupational Hismentioning
confidence: 99%